Until I could be sure: how I stopped the death penalty in Illinois - Ryan, George H. (Rowman & Littlefield, 2020)
"Until I Could Be Sure chronicles how Governor George Ryan set aside his prior beliefs-and pressure from the public and politicians-to take on a culture and a system of punishment that Americans long have grappled with, even as much of the rest of the civilized world has consigned it to the dustbin of history"--